THE INFORMATION SPACE OF THE GLOBAL NETWORK: SOCIAL-PHILOSOPHICAL ASPECT - Ягодзінський, С. М. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
Forming of an information component in the architecture of the modern information global network is explored in the article.